2002
DOI: 10.1021/ic010448g
|View full text |Cite
|
Sign up to set email alerts
|

Pyrazolyl-Bridged Iridium Dimers. 18.1 Influence of Metal−Metal Bonding on the Geometry of Diiridium(II) Adducts and Hydrido-diiridium Complexes Formed from the Diiridium(I) Prototype [Ir(μ-pz)(PPh3)(CO)]2 (pzH = Pyrazole) by Dihydrogen Addition or Protonation

Abstract: Slow uptake of molecular dihydrogen by the diiridium(I) prototype [Ir(mu-pz)(PPh(3))(CO)](2) (1: pzH = pyrazole) is accompanied by formation of a 1,2-dihydrido-diiridium(II) adduct [IrH(mu-pz)(PPh(3))(CO)](2) (2), for which an X-ray crystal structure determination reveals that (unlike in 1) the PPh(3) ligands are axial, with the hydrides occupying trans coequatorial positions across the Ir-Ir bond (2.672 A). Reaction with CCl(4) effects hydride replacement in 2, affording the monohydride Ir(2)H(Cl)(mu-pz)(2)(P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 24 publications
0
7
0
1
Order By: Relevance
“…70 X-ray structure determination showed that the two PPh 3 ligands would axially coordinate to the iridium(II) metal centers, while the hydrides would occupy the trans coequatorial positions along the intramolecular Ir(I)•••Ir(I) bond, the distance of which was determined to be 2.672 Å. 70 Further reaction with CCl 4 would replace the hydride to afford the monohydride complex, [Ir 2 (PPh 3 ) 2 (CO) 2 (μ-pz) 2 H(Cl)], with an intramolecular Ir-(I)•••Ir(I) separation of 2.683 Å. As evidenced by the X-ray crystal structure, the hydride was equatorial and the triphenylphosphine was in axial position of one of the metal centers.…”
Section: Light-emitting Iridium(i) Self-assembled Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…70 X-ray structure determination showed that the two PPh 3 ligands would axially coordinate to the iridium(II) metal centers, while the hydrides would occupy the trans coequatorial positions along the intramolecular Ir(I)•••Ir(I) bond, the distance of which was determined to be 2.672 Å. 70 Further reaction with CCl 4 would replace the hydride to afford the monohydride complex, [Ir 2 (PPh 3 ) 2 (CO) 2 (μ-pz) 2 H(Cl)], with an intramolecular Ir-(I)•••Ir(I) separation of 2.683 Å. As evidenced by the X-ray crystal structure, the hydride was equatorial and the triphenylphosphine was in axial position of one of the metal centers.…”
Section: Light-emitting Iridium(i) Self-assembled Materialsmentioning
confidence: 99%
“…As evidenced by the X-ray crystal structure, the hydride was equatorial and the triphenylphosphine was in axial position of one of the metal centers. 70 However, at another metal center, the chloride would be axial as found in the symmetrically substituted product, [Ir(Cl)(PPh 3 )(CO)(μ-pz)] 2 (Ir(I)•••Ir(I) distance = 2.754 Å), that was formed by the reaction of [Ir(PPh 3 )(CO)(μ-pz)] 2 with CCl 4 . 70 Bis(carbonyl)acetylacetonatoiridium (I), [Ir(CO) 2 (acac)], is another class of well-known complexes that has been utilized as a precursor in the preparation of metal films and coatings via chemical vapor deposition (CVD).…”
Section: Light-emitting Iridium(i) Self-assembled Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous examples of the protonation reactions of dinuclear iridium complexes include the reactions of [Ir 2 (μ-L) x (CO) 2 (PR 3 )] (L = Pz, x = 2; L = 1,8-diamidonaphthalene, x =1) with HBF 4 . The resulting cationic mono-hydride compounds were found to be active species for the addition of dihydrogen, water, and methanol . We describe in this paper the preparation of unusual dihydride Ir(III)/Ir(III) complexes and the striking influence of the chloride versus trifluoroacetic anions in the stabilization of intermediate Ir(II)/Ir(II) or Ir(I)/Ir(III) monoprotonated complexes.…”
Section: Introductionmentioning
confidence: 99%
“…-V(1)-N(5) 85.66(14) O(1)-V(1)-N(7) 91.29(15) O(1)-V(1)-N(1) 94.32(14) O(2)-V(1)-N(7) 87.41(13) O(2)-V(1)-N(1) 86.87(13) N(5)-V(1)-N(7) 90.22(14) N(5)-V(1)-N(1) 172.34(16) N(1)-V(1)-N(7) 91.12(14) O(1)-V(1)-N(3) 93.35(15) N(3)-V(1)-N(7)175.32(16) …”
unclassified